ANALISIS PENGENDALIAN INTERNAL COMMITTEE OF SPONSORING ORGANIZATIONS TERHADAP PIUTANG USAHA PADA CV. KOMBOS MANADO 1 - Liho, Christian Jeanry; Pangemanan, Sifrid; Pusung, Rudy (Universitas Sam Ratulangi, 2018)
Accounts receivable is an element of current assets in the company's balance sheet arising from the sale of goods, services or lending to debtors whose payments are generally given within 30 days to 90 days. This research was conducted to analyze internal control committee of sponsoring organizations to accounts receivable at CV. Kombos Manado 1 and analyze the factors of delay in payment of accounts receivable on CV. Kombos Manado 1. The research method used is descriptive method and the type of research used is qualitative descriptive. The results obtained that the Internal Control Committee Of Sponsoring Organizations Against Accounts Receivable on CV. Kombos Manado 1 has been running quite well. Of the 5 (five) internal control components of the committee of sponsoring organizations, namely the control environment, risk assessment, control procedures, monitoring, information and communication, only a weakly categorized control environment. The obstacle faced by the receivable officer is the delay of payment of receivable from the customer. There are 2 (two) factors the customer is late to pay the receipt of the negligence of the company and negligence from the customer (insurance).Keywords: Analysis, Internal Control, Accounts Receivable.